2023
DOI: 10.3389/fpls.2023.1096842
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and elicited production of triterpenoid saponin glycosides and stigmasterol via precursor and elicitor feeding in Bacopa floribunda (R.Br.) Wettst.—A potential nootropic herb

Abstract: Bacopa floribunda (Family: Plantaginaceae) is used in folklore medicines for the management of cognitive dysfunction. It has nootropic, antiaging, anti-inflammatory, anti-cholinesterase, and antioxidant properties. We developed an efficient and reproducible protocol for in vitro propagation of B. floribunda using the nodal explants. We assessed the effects of Murashige and Skoog (MS) medium fortified with various plant growth regulatory substances (PGRs), a precursor, and elicitors and their optimal combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…However, the variation was observed in the contents according to the elicitor treatment (Figures 3-6). Elicitor-mediated production of bioactive metabolite production has been reported by several researchers (Ahire et al, 2014;Chavan et al, 2021;Otari et al, 2023). The present results revealed that a lower NaCl concentration (50 mM) supported elevated mangiferin content in root, stem and leaves.…”
Section: Discussion Discussion Discussionsupporting
confidence: 78%
“…However, the variation was observed in the contents according to the elicitor treatment (Figures 3-6). Elicitor-mediated production of bioactive metabolite production has been reported by several researchers (Ahire et al, 2014;Chavan et al, 2021;Otari et al, 2023). The present results revealed that a lower NaCl concentration (50 mM) supported elevated mangiferin content in root, stem and leaves.…”
Section: Discussion Discussion Discussionsupporting
confidence: 78%
“…Aculeatiside A and B accumulations in the callus of Solanum aculeatissimum were enhanced in solid medium with 0.1 mg/L NAA [ 61 ]. Furthermore, the application of exogenous auxins induced higher total saponins and saponin glycoside contents in the roots of Panax ginseng [ 62 ], Gypsophila paniculata roots [ 24 ], and Bacopa floribunda micropropagated plantlets [ 63 ]. Auxins can also show positive effects on the phenolic production in root cultures.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the adventitious induction, the effects of NAA on the elevated TPC have been proved in Salvia miltiorrhiza [ 55 ]. The application of exogenous auxins has demonstrated the improved content of total saponin in several plant species [ 62 , 63 ]. The efficiency of NAA in influencing these phytochemical contents may be attributed to the increased enzyme activities associated with the biosynthesis pathways of these compounds [ 56 ].…”
Section: Resultsmentioning
confidence: 99%